AMENGUAL COLL, G. (2021). La solidaridad. Historia, concepto, propuesta. Madrid: Comillas - Ortigosa , Andrés (Daimon Revista Internacional de Filosofia, 2025)
Reseña de AMENGUAL COLL, G. (2021). La solidaridad. Historia, concepto, propuesta. Madrid: Comillas.